Diversifikasi Pengolahan Jamur Tiram pada Kelompok Tani Saraso, Kenagarian Batu Balang, Kecamatan Harau, Kabupaten Lima Puluh Kota - Tety Desrita Handayani; Mimi Harni; Fidela Violalita; Nurzarrah Tazar (Warta Pengabdian Andalas, 2020)
Oyster mushrooms are widely cultivated by Saraso farmer group Kenagarian Batu Balang, Harau District, Lima Puluh Kota Regency. The purpose of the activity was to increase knowledge and skills and empower the women of the Saraso Farmers Group, in the diversification of processed oyster mushroom products in order to increase the selling value. So far, the oyster mushrooms they cultivate are sold in fresh mushrooms, and only a few sell in processed food. The hope is that with this activity, the community can make various processed oyster mushrooms to add value to the sale which is expected to raise the family economy. The activity method was carried out by demonstration and hands-on practice. The results of community service activities showed that the women of the Saraso farmer group are able to process oyster mushrooms into various ready-to-consume products. Various processed mushrooms are made, namely Dendeng oyster mushroom, oyster mushroom beef, oyster mushroom satay, oyster mushroom shredded and additional materials, namely making sauces and chili sauce. This activity succeeded in arousing the motivation of the Saraso farmer groups in making variations of processed oyster mushrooms.